Associations between lower limb forces and jab punch force in elite male amateur boxers - Pádecký, J.; Kubový, P.; Brich, J.; Jebavý, R.; Tufano, J. (The Journal of Strength and Conditioning Research, 2021)
The most common boxing punch is the straight jab, which is assumed to be initiated by legs, followed by slight trunk rotation, shoulder flexion and elbow extension. However, to our best knowledge, there is no evidence supporting the association between lower limb force with jab force. Purpose: Therefore, the purpose of this study was to quantify lower limb forces and their association with jab peak force (PFJAB). Methods: Twelve elite male amateur boxers (80.4 ± 11.1 kg, 181.6 ± 7.1 cm, 8.0 ± 5.9 years of boxing experience) participated in this study, which took place over 2 laboratory visits: familiarization and experimental. During the experimental visit, subjects completed a general warm up followed by a boxing-specific warm up. After 4 minutes of rest, subjects performed 1 maximal effort jab while standing on 2 tri-axial force plates (Kistler group, Switzerland) in a self-selected stance. Subjects were instructed to punch the center of a separate tri-axial force plate that was suspended in the air at chin level (Kistler group, Switzerland). The sampling frequency of all force plates was set at 12,000 Hz. Synchronized video recordings were used to identify the start of the punch using Qualisys Motion Tracking Manager (QTM) with a sampling frequency of 500 fps. All forces were transformed into relative forces (Newtons of force per kilogram of body mass). Standard multiple regression was used for 2 models separately, which included rear leg peak forces (PFRL) in the ×, y, and z directions as independent variables for one model, and lead leg peak forces (PFLL) in the x, y, and z directions as independent variables for the second model, both with PFJAB as the dependent variable. Results: PFJAB was 0.81 ± 0.15 N/kg, PFRL in x, y and z direction (0.22 ± 0.09 N/kg, -0.07 ± 0.06 N/kg and 0.86 ± 0.32 N/kg, respectively) and PFLL in x, y and z direction (-0.30 ± 0.27 N/kg, 0.19 ± 0.16 N/kg and 0.81 ± 0.46 N/kg, respectively). Standard multiple regression model for PFRL resulted in R = 0.55, R2 = 0.30, and adjusted R2 = 0.04 with non-significant F change 0.38, while the model for PFLL resulted in R = 0.44, R2 = 0.19, and adjusted R2 = -0.10 with non-significant F change of 0.60. Standardized Beta coefficients, correlations, and collinearity statistics are present in Table 1. Conclusions: Leg force only explained only a small, insignificant variance in PFJAB, suggesting that other variables such as trunk rotation, arm extension, and effective mass may be larger contributors to PFJAB. The most explained variance from the dynamics of the legs may be with PFRL in the z and x directions. However, it should be noted that these fighters were well-trained boxers, and the contribution of the legs may differ between experience levels. Practical Application: Strength and conditioning specialists should implement a combination of upper body pushing, lower body lateral, and rotational exercises within a periodized training plan in order to increase PFJAB.